Role play - An effective tool to teach communication skills in pediatrics to medical undergraduates - Bindu T Nair (Wolters Kluwer Medknow Publications, 2019)
PURPOSE: Communication skills are essential for medical practice throughout the life of a doctor. Traditional undergraduate medical teaching in pediatrics focuses on teaching students with theoretical and practical knowledge of diseases, their diagnosis, and treatment modalities. This study was done to use role play as a tool to teach basic communication skills to the final-year undergraduate students in pediatrics and to assess perceptions of students and faculty for using role play to teach counseling and communication skills in pediatrics. METHODS: It was an observational, questionnaire-based study conducted in the Department of Pediatrics on the final-year medical undergraduates. Two modules for role play on common pediatric topics were designed and role play was conducted. At the end of the session, student and faculty feedback were taken by a prevalidated questionnaire with both close (using the 5-point Likert scale) and open-ended questions. In pre- and post-role play sessions, communication skills assessment scoring was done. Statistical evaluation of the collected data was then carried out using SPSS 22. RESULTS: A total of 98 final-year students participated in this study. Role play was found to be the most preferred tool (33%) for teaching communication skills to the students. Majority of the students (88.78%) and faculty (91.67%) felt that role play helped in teaching communicating skills. Comparison of pre- and post-role play scores on communication skills showed statistically significant improvement (P < 0.001). CONCLUSION: Role play can be used as an effective tool to teach communication skills to undergraduate medical students in pediatrics.